Water Flow, Temperature, and PH Monitoring Based on the Internet of Things(IoT) - Ramli, Ibrahim Ariff; Dirman Hanafi, (Evolution in Electrical and Electronic Engineering, 2022)
The hardware of the water flow sensor was successfully designed. It is connected with the pipe at home to get the flow rate and volume of water. The temperature sensor is placed in a container with contains different water temperatures. The PH sensor was also placed on a container containing three different solutions. The designed water flow sensor was successfully tested using a water pipe at home. The flow rate and volume successfully display on the Blynk application. The flow rate is displayed on the gauge widget on Blynk and the volume is displayed on the LCD widget. The temperature sensor is well tested in a container that contains hot water and cold water. The value of temperature water is successful display on the LCD widget on the Blynk application. The designed PH sensor was successfully tested in a container that contain vinegar solution, pure water solution, and soap solution. The value of PH is successful display on the LCD widget on Blynk. The collected data of flow rate on the first test at three locations shows between 100 L/h and 266 L/h. For temperature, the highest value of temperature is 68°C obtained from thermometer while using temperature sensor is 70°C which is average error is 5%. For the PH sensor, the first test is using vinegar solution. The lowest value obtained from the sensor is 2.322 and the highest value obtained is 2.347. The second test is using a pure water solution. The lowest value obtained from the sensor is 7.412 and the highest value obtained is 7.422. The third test is using the solution. The lowest value obtained from the sensor is 10.91 and the highest value obtained is 10.98.